Effective crime reduction strategies international perspectives - Albrecht, James F.; Das, Dilip K., 1941-; International Police Executive Symposium (Boca Raton : CRC Press, 2011)
" Police worldwide are finding it increasingly difficult to prevent crime and maintain public safety and a sense of security while dealing with decreasing budgets and personnel. The exchange of effective crime fighting principles and proven best practices is crucial to helping them succeed. Drawn from the proceedings at the 2005 IPES meeting in the Czech Republic on effective crime prevention, this book addresses the impact of terrorism and transnational crime on law enforcement in the U.S. and Europe, the effects of democratic reforms on policing, and the positive influence of the unionization of police forces. It also reviews counterterrorism, border control, transnational criminality, measurement of police effectiveness, and the investigation of juvenile crimes. "--
pt. 1. Critical issues in European law enforcement -- pt. 2. Contemporary concerns : policing in the United States and Canada -- pt. 3. Paradigm shifts : policing as a democracy evolves -- pt. 4. Revising traditional law -- pt. 5. The positive influence of unionization on police professionalism -- pt. 6. Significant issues facing twenty-first century law enforcement.
"Enhancing law enforcement professionalism, effectiveness and leadership in the 21st century".
Includes bibliographical references and index.
Description based on metadata supplied by the publisher and other sources.
Electronic reproduction. Santa Fe, Arg.: elibro, 2020. Available via World Wide Web. Access may be limited to eLibro affiliated libraries.
Keywords: Crime prevention -- Congresses; Transnational crime -- Prevention -- Congresses; Terrorism -- Prevention -- Congresses; Electronic books